“EFFECT OF TASK-ORIENTED TRAINIG ALONG WITH CONVENTIONAL THERAPY ON IMPROVING BALANCE IN POST STROKE INDIVIDUALS” - Pathak, Pranjal A.; Varadharajulu, G. (International Journal of Psychosocial Rehabilitation, 2020)
A comparative study was conducted to find out the effect of Task-Oriented Training along with the conventional therapy on improving balance in Stroke individuals. The study was conducted on 20 subjects. Subjects medically diagnosed as first ever acute phase ischemic Stroke & both sexes were included in the study. Using chit method the subjects were split into 2 groups. A thorough Neurological examination was done. Pre-intervention in both groups the subjects were scored on the outcome measures berg balance scale for balance and modified barthel index for functional performance. Conventional physiotherapy was given to the Control group & 1 hour of Task-Oriented Training along with the conventional physiotherapy to the Experimental group for 12 weeks. Reassessment was taken post 6 weeks and post 12 weeks of intervention in both the groups for balance and functional performance. The results were derived using the appropriate statistical tests. The study shows that there was an extremely significant improvement in balance in both the groups, but when compared in between the groups Task-Oriented Training along with conventional training showed comparatively better improvement at the end of 12 weeks. Also there was an extremely significant improvement in functional performance within the groups. When compared in between the groups Task-Oriented Training along with conventional training showed better as well as earlier improvement in functional performance i. e. post 6t" week and post 12t" week assessment both showed significant in between group difference with experimental group proving to be better. CONCLUSION - The present study supports the use of Task-Oriented Training for Rehabilitation of acute Stroke individuals to improve balance and functional performance. These findings may be applied to Rehabilitate other Stroke individuals with due considerations given to the limitations of the present study. Keywords: Task- Training, Conventional Therapy, Stroke A comparative study was conducted to find out the effect of Task-Oriented Training along with the conventional therapy on improving balance in Stroke individuals. The study was conducted on 20 subjects. Subjects medically diagnosed as first ever acute phase ischemic Stroke & both sexes were included in the study. Using chit method the subjects were split into 2 groups. A thorough Neurological examination was done. Pre-intervention in both groups the subjects were scored on the outcome measures berg balance scale for balance and modified barthel index for functional performance. Conventional physiotherapy was given to the Control group & 1 hour of Task-Oriented Training along with the conventional physiotherapy to the Experimental group for 12 weeks. Reassessment was taken post 6 weeks and post 12 weeks of intervention in both the groups for balance and functional performance. The results were derived using the appropriate statistical tests. The study shows that there was an extremely significant improvement in balance in both the groups, but when compared in between the groups Task-Oriented Training along with conventional training showed comparatively better improvement at the end of 12 weeks. Also there was an extremely significant improvement in functional performance within the groups. When compared in between the groups Task-Oriented Training along with conventional training showed better as well as earlier improvement in functional performance i. e. post 6t" week and post 12t" week assessment both showed significant in between group difference with experimental group proving to be better. CONCLUSION - The present study supports the use of Task-Oriented Training for Rehabilitation of acute Stroke individuals to improve balance and functional performance. These findings may be applied to Rehabilitate other Stroke individuals with due considerations given to the limitations of the present study.